mGluR-dependent plasticity in rodent models of Alzheimer’s disease - Valdivia, Gonzalo; Ardiles, Alvaro O.; Idowu, Abimbola; Salazar, Claudia; Lee, Hey-Kyoung; Gallagher, Michela; Palacios, Adrian G.; Kirkwood, Alfredo (Frontiers in Synaptic Neuroscience, 2023)
NLong-term potentiation (LTP) and depression (LTD) are currently the most comprehensive models of synaptic plasticity models to subserve learning and memory. In the CA1 region of hippocampus LTP and LTD can be induced by the activation of either NMDA receptors or mGluR5 metabotropic glutamate receptors. Alterations in either form of synaptic plasticity, NMDR-dependent or mGluR-dependent, are attractive candidates to contribute to learning deficits in conditions like Alzheimer’s disease (AD) and aging. Research, however, has focused predominantly on NMDAR-dependent forms of LTP and LTD. Here we studied age-associated changes in mGluR-dependent LTP and LTD in the APP/PS1 mouse model of AD and in Octodon degu, a rodent model of aging that exhibits features of AD. At 2 months of age, APP/PS1 mouse exhibited robust mGluR-dependent LTP and LTD that was completely lost by the 8th month of age. The expression of mGluR protein in the hippocampus of APP/PS1 mice was not affected, consistent with previous findings indicating the uncoupling of the plasticity cascade from mGluR5 activation. In O. degu, the average mGluR-LTD magnitude is reduced by half by the 3rd year of age. In aged O. degu individuals, the reduced mGluR-LTD correlated with reduced performance in a radial arm maze task. Altogether these findings support the idea that the preservation of mGluR-dependent synaptic plasticity is essential for the preservation of learning capacity during aging.